Scurvy in a Child with Cerebral Palsy- The Forgotten Vitamin Deficiency: A Case Report (Global Journal of Medical Research, 2014)
Scurvy was the first vitamin deficiency disease to be described. However it is seldom seen in the pediatric age group. It is often missed, especially amongst physically and mentally disabled patients who form a high risk group for this disease. Scurvy can present with a varied spectrum of signs and symptoms. Here we present a case of scurvy in a child with cerebral palsy.